Herd Behavior in Financial Markets : A Review - Sharma, Sunil (IMF Working Papers; Working Paper ;, 2000)
Policymakers often express concern that herding by financial market participants destabilizes markets and increases the fragility of the financial system. This paper provides an overview of the recent theoretical and empirical research on herd behavior in financial markets. It addresses the following questions: What precisely do we mean by herding? What could be the causes of herd behavior? What success have existing studies had in identifying such behavior? And what effect does herding have on financial markets?.